Diversity of grasshopper in Lingsar Vegetable Field, West Lombok - Mohammad Liwa Ilhamdi; Agil Al Idrus; Didik Santoso; Ahmad Raksun (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Vegetables are one of the commodities that support the economic sector. Many factors affect the success rate of vegetable production, including pests. Grasshoppers are herbivorous insects that have the potential as pests that will affect crop yields, especially vegetables. This study aims to determine the diversity of grasshoppers in the vegetable field of Bug-Bug Village, Lingsar District, West Lombok. Sampling was carried out on vegetables with differences in plant age, namely 1, 2, and 3 months using the sweeping net method in the morning (07.00-10.30) around the edge and middle of the vegetable field. It is found that there are eight types of grasshoppers in 2 sub-orders and three families (Acrididae (6 species), Pyrgomorphidae (1 species), Tettigoniidae (1 species)). Atractomorpha crenulata and Oxya japonica were grasshopper species with the highest relative abundances of 42% and 29%, respectively. The analysis showed that the diversity index (H') of grasshoppers found in the research location was 1.5445.